Health-related expenses in the Polish household budget - Skrzypczak, Zofia (Polish Journal of Public Health, 2010)
In most high-income countries of the ‘old’ European Union the share of personal health spending has been gradually decreasing whereas in the ‘new’ EU member states, including Poland, a growing trend in private charges has been observed. Currently (2009), private expenditures on healthcare in Poland reach 30% of the total health outlays. Household expenditures take the predominant position among all private health-related expenses. Polish Central Statistical Office carries out research of household budgets on a yearly basis. The results show acceleration of health-related expenses regarded as part of individual consumption. Medication makes up approximately 60% of private health-related expenses.